Teachers’ identities under the magnifying glass in the EFL field: Crossing intellectual borders - Méndez, Pilar; Clavijo-Olarte, Amparo (Colombian Applied Linguistics Journal, 2017)
As a coeditor of CALJ, I would like to draw your attention to the rising importance of identity studies in the EFL setting and their contribution to the field. The Socratic imperative “know thyself” has inspired teacher researchers around the world (Benwell & Stokoe, 2006; Cheung, 2015; Johnson & Golombek, 2016; Norton, 2013) to raise awareness towards knowledge-power relations affecting our own constitution as subjects (Foucault, 1980). From a post-structuralist view, the comprehension of identity as something not given but constituted has illuminated a type of research more interested in revealing how interior and exterior forces—in Deleuze’s (1993) words—influence our constitution as subjects of a practice. In the field of EFL, research examining identity contributes to the understanding of who English teachers and learners are and how these identities are related to the teaching and learning process.